Elemental sulfur recommendation for pH reduction in soils from Southern Brazil - Daniel J. Dall’Orsoletta; Gilmar L. Mumbach; Fernando M. Brignoli; Luciano C. Gatiboni (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The elemental sulfur (S0) application may reduce soil pH, benefiting plants adapted to acid conditions and lessening problems of overliming. Nevertheless, there is no official recommendation for its application. The objective of the study was to quantify the S0 doses required to reduce the pH of soils from Southern Brazil. The experiment was carried out in the laboratory in a factorial scheme (5 × 5), with a completely randomized design and three replicates. The treatments consisted of five soils, and five doses of S0, corresponding to 0, 50, 100, 150, and 200% of the estimated dose need to reach pH 4.0. The applied doses of S0 resulted in reduction of pH and base saturation (V%) and increase of potential acidity (H + Al). These effects, however, were reduced due to the low rate of oxidation of the S0 applied (0.76-3.36%). The soil variables correlated with S0 oxidation were Mg2+ (0.86***), Al3+ (-0.82***), H + Al (-0.89***), V% (0.68***) and aluminum saturation (m%) (-0.87***). In the evaluated soils the oxidation of 50 kg ha-1 of S0 was required to reduce one unit of pH in H2O.